Exploration of turn-positive RT-PCR results and factors related to treatment outcome in COVID-19: A retrospective cohort study. Issue 1 (31st December 2020) - Xiao, Yong; Shi, Xiao; She, Qian; Chen, Qi; Pan, Hong; Zhang, Jin; Liu, Xiaojiao; Wu, Haiyan; Jin, Wenfei; Ke, Ge; Liu, Shuzhong; Li, Jiao; et al.
ABSTRACT: The cause of some patients with negative RT-PCR results experienced turn-positive after treatment remains unclear. In addition, understanding the correlation between changes in clinical data in the course of COVID-19 and treatment outcomes is of great importance in determining the prognosis of COVID-19. To perform cause analysis of RT-PCR turn-positive and the effective screening factors related to treatment outcome in COVID-19. Clinical data, including clinical manifestations, laboratory tests, radiography results, treatment methods and outcomes, were retrospectively collected and analyzed from January to March 2020 in Renmin Hospitals of Wuhan University. 116 COVID-19 patients (40 in recurrent group, 29 in recovered group and 47 in unrecovered group) were recruited. In the recurrent group, white blood cell, Neutrophils, prothrombin time, activated partial thromboplastin time, CD3, CD4, CD8, ratio of CD4/CD8, IgG and C4 complement were of significant difference among the baseline, negative and turn-positive time points. CD19 and CT scan results were found notable difference between recurrent group and recovered group. Odds from CD3, CD4, CD8, CD19, IgM, C3 complement, C4 complement and CT scan results validated associations with clinical outcomes of COVID-19. The so-called recurrence in some COVID-19 patients may be due to the false-negative of nucleic acid test results from nasopharyngeal swabs. Levels of CD3, CD4, CD8, CD19, IgM, C3 complement, C4 complement and CT results were significantly correlated with the outcome of COVID-19. The cellular immunity test could be beneficial to further screen the reliability of RT-PCR test on the basis of CT images.